ANALISIS ELASTISITAS DAN TINGKAT KESULITAN REALISASI PENERIMAAN SUMBER KEUANGAN DAERAH Dl KABUPATEN SLEMAN - Prawoto, Nano (Jurnal Ekonomi & Studi Pembangunan, 2006)
This research focuses on measurement aspect of elasticity and difficulty rate of local receipt realization in Sleman Regency. The analysis which developed is regression model by partial adjustment model (PAM). The result of this Study shows that the elasticity of all models more than I (E 1) or elastic. It means that local finance interdependence on central payment in long term is relatively decrease, assumed there is an economic growth (GDRB). This studyConcludes that coefficient. _ 1 or close to zero means the difficulty rare is relatively high, because it cannot operate the local receipt planning as the target. It is shown that local receipt administration relatively bad. So that this research recommended that the local governments have to increase an economic growth for increasing the local receipt, and an improvement on professionalism of human resources.